Secrets of the new Web Beyond Google.
10 of the most useful web-hosted applications.
Keywords: Electronic mail messages; Yahoo! (Computer file); Zoho Office; Windows Hotmail Live; Yahoo Mail; Planzo; Remember the Milk; ThinkFree Office; Scribd; Windows Live SkyDrive; Pixenate; MediaMaster